2015
DOI: 10.1086/684297
|View full text |Cite
|
Sign up to set email alerts
|

Decriminalizing Delinquency: The Effect of Raising the Age of Majority on Juvenile Recidivism

Abstract: In the last decade, a number of states have expanded the jurisdiction of their juvenile courts by increasing the maximum age to 18. Proponents argue that these expansions reduce crime by increasing access to the beneficial features of the juvenile justice system. Critics counter that the expansions risk increasing crime by reducing deterrence. In 2010, Illinois raised the maximum age for juvenile court for offenders who commit a misdemeanor. By examining the effect of this law on juvenile offenders in Chicago,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Beyond Connecticut, these results also suggest that public safety may not be the primary lens through which this policy initiative should be viewed (Brown, ; NCRSJJS, ; Rubin, ). Even though this study is the first such study to include an examination of “raise the age” at the aggregate level and, therefore, to show no impact on the overall crime equation, it is the second study to show no impact on a measure of criminal offending (Loeffler and Grunwald, ). Future research on “raise‐the‐age” and other related policy initiatives (e.g., juvenile decarceration) could usefully be focused on the nonpublic‐safety effects of these policies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Beyond Connecticut, these results also suggest that public safety may not be the primary lens through which this policy initiative should be viewed (Brown, ; NCRSJJS, ; Rubin, ). Even though this study is the first such study to include an examination of “raise the age” at the aggregate level and, therefore, to show no impact on the overall crime equation, it is the second study to show no impact on a measure of criminal offending (Loeffler and Grunwald, ). Future research on “raise‐the‐age” and other related policy initiatives (e.g., juvenile decarceration) could usefully be focused on the nonpublic‐safety effects of these policies.…”
Section: Discussionmentioning
confidence: 96%
“…The results of an early investigation of Connecticut's raise‐the‐age law, which involved comparing 16‐year‐olds arrested before and after the law change, suggested that it produced large reductions in juvenile recidivism (Justice Policy Institute, ). A more recent evaluation of Illinois’ law change, which included counterfactual comparison groups consisting of juveniles arrested weeks before the Illinois law change or weeks before their 17th birthday after the law change, yielded little evidence of an effect on juvenile recidivism (Loeffler and Grunwald, ). Although many of the outstanding methodological concerns of estimating the effects of raise‐the‐age policies at the individual level were addressed in this more recent study, identifying the aggregate‐level crime effects of raise‐the‐age policies remains a difficult challenge for two reasons.…”
mentioning
confidence: 99%
“…Several papers on juvenile offenders in other states exploit sharp changes in sentence severity that occur at age 18 and find similar results. Guarin, Medina, and Tamayo (2013) and Loeffler and Grunwald (2015) conclude that more severe penalties reduce recidivism. Lee and McCrary (2017) also obtain negative estimates of sentence severity on recidivism, but with a magnitude so small as to lack much economic significance.…”
Section: Rd Studies Of Incarceration Effectsmentioning
confidence: 99%
“…Yet, this consideration suggests that the change may have a delayed rather than an immediate effect (amplified by the common delay between arrest and court processing), and that it would be desirable to investigate the effects of the change on reoffending rather than on offending. Unlike Loeffler and Grunwald (), for example, the article by Loeffler and Chalfin () does not investigate reoffending or attempt to determine the fraction of crimes that represents first offending as opposed to reoffending.…”
Section: Effects Of Raising the Minimum Age For Adult Court In Connecmentioning
confidence: 99%